Algebraic Double Entry. - Mead, George C.; Murphy, George J. (The Accounting Review, 1970)
The foregoing exposition allows us a) to trace through the effects of transactions in and on the algebraic equation; b) to demonstrate both the correspondence of the algebraic equation with the double entry-journal entry form of recording, and the articulation of the income and balance sheet statements; and c) to elaborate the calculations of ROl and Source and Application of Funds by means of the algebraic equation. The algebraic equation is therefore an alternative and hopefully useful alternative pedagogical method.